Evolution over 62 years: an analysis of sexism in the lyrics of the most-listened-to songs in Spain - Laura Casanovas-Buliart; Priscila Alvarez-Cueva; Carlos Castillo (Cogent Arts & Humanities)
Sexism against women remains an entrenched problem, manifested in contemporary cultural production worldwide. Since cultural production can be understood as both a mirror for and a reflection of the society where it is inserted, the persistence of sexism in music might rather represent how sexist our society is. The present work aims to analyze the evolution of sexism towards women among the most listened to music lyrics during the past six decades in Spain. To perform a large-scale analysis, automatic text classification based on manually labeled training data is used to categorize music lyrics as sexist or non-sexist. The findings show that sexism has always been present in song lyrics in Spain, and the presence of it has increased considerably in the music made available through streaming platforms over the last decade. This research has the potential to help detect, monitor, and mitigate sexist biases, while also advancing the automation of some aspects of content analysis within the realm of cultural studies.